Left-sided gastroschisis associated with situs inversus totalis - Marcelo Francetich Nam; Julianna Sayuri Kaneko; Priscila Marques Intelizano; Rita Medeiros Ferreira; Natalia Meijas Oliveira; Maria Julia Mendonça; Adriana Orsetti Goularth; Luis Felipe Araújo Campos; Roberto Antonio Mastroti (Elsevier, 2018)
We present a case of gastroschisis associated with situs inversus totalis in a female neonate. To our knowledge, only a few case reports of left-sided gastroschisis have been reported in the world literature, especially one associated with situs inversus. Keywords: Left-sided gastroschisis, Situs inversus, Newborn